Evolution of quality indicators in acute stroke during the RACECAT Trial: Impact in the general population. Issue 2 (February 2023) - Olivé-Gadea, Marta; Pérez de la Ossa, Natalia; Jovin, Tudor; Abilleira, Sonia; Jiménez, Xavier; Cardona, Pere; Chamorro, Angel; Flores, Alan; Silva, Yolanda; Purroy, Francesc; Martí-Fabregas, Joan; Rodríguez-Campello, Ana; et al.
Background: Acute ischemic stroke patients not referred directly to a comprehensive stroke center (CSC) have reduced access to endovascular treatment (EVT). The RACECAT trial is a population-based cluster-randomized trial, designed to compare mothership and drip-and-ship strategies in acute ischemic stroke patients outside the catchment area of a CSC. Aims: To analyze the evolution of performance indicators in the regions that participated in RACECAT. Methods: This retrospective longitudinal observational study included all stroke alerts evaluated by emergency medical services in Catalonia between February 2016 and February 2020. Cases were classified geographically according to the nearest SC: local SC (Local-SC) and CSC catchment areas. We analyzed the evolution of EVT rates and relevant workflow times in Local-SC versus CSC catchment areas over three study periods: P1 (February 2016 to April 2017: before RACECAT initiation), P2 (May 2017 to September 2018), and P3 (October 2018 to February 2020). Results: We included 20603 stroke alerts, 10, 694 (51.9%) of which were activated within Local-SC catchment areas. The proportion of patients receiving EVT within Local-SC catchment areas increased (P1 vs. P3: 7.5% (95% confidence interval (CI), 6.4–8.7) to 22.5% (95% CI, 20.8–24.4) p  < 0.001). Inequalities in the odds of receiving EVT were reduced for patients from CSC versus Local-SC catchment areas (P1: odds ratio (OR) 3.9 (95% CI, 3.2–5) vs. P3: OR 1.5 (95% CI, 1.3–1.7) In Local-SC, door-to-image (P1: 24 (interquartile range (IQR) 15–36), P2: 24 (15–35), P3: 21 (13–32) min, p  < 0.001) and door-to-needle times (P1: 42 (31–60), P2: 41 (29–58), P3: 35 (25–50) p  < 0.001) reduced. Time from Local-SC arrival to groin puncture also decreased over time (P1: 188 [151–229], P2: 190 (157–233), P3: 168 (127–215) min, p  < 0.001). Conclusion: An increase in EVT rates in Local-SC regions with a significant decrease in workflow times occurred during the period of the RACECAT trial.